Numerical simulation of biomass gasification in fluidized bed gasifiers. (1st April 2023) - Yang, Miao; Mousavi, Seyed Morteza; Fatehi, Hesammedin; Bai, Xue-Song
Abstract: Numerical simulation of biomass gasification in fluidized bed reactors faces several challenges including proper modeling of the physical and chemical processes involved in the gasification and numerical stiffness of the two-phase dense particle flow problem. In this paper, the multi-phase particle-in-cell (MP-PIC) model coupled with a recently developed distribution kernel method (DKM) and a new one-step pyrolysis model are employed to investigate biomass gasification in two lab-scale fluidized bed gasifiers (FBGs). The results are evaluated by comparing with the results from the Particle Centroid Method (PCM) and experimental measurements. The performance of DKM is shown to improve the robustness of the model and the new pyrolysis model is shown to improve the sensitivity of the yields of gasification products to operating temperature. The simulation results using the new pyrolysis model agree well with the experimental data under different gasification conditions. The model is shown to be able to capture the trend of gas products with respect to variations of steam/biomass ratio (SR) and operating temperature ( T r ). The mechanisms of the formation of gas products are analyzed based on the numerical results. By increasing the SR and T r, the production of H 2 and CO 2 is shown to increase while the production of CO and CH 4 to decrease. It is shown that varying the steam/biomass ratio in the range of 0.8 ∼ 2.0 has a minor effect on the pyrolysis process and heterogeneous reactions, while homogeneous reactions are significantly affected, leading to changes in the final composition of the gas products. Varying the gasifier temperature T r has on the other hand a crucial effect on the pyrolysis process and as such a significant impact on the gasification products and carbon conversion. Highlights: An empirical one-step model was developed for biomass pyrolysis. Prediction of gasification products at varying operating temperatures was improved. Impact of steam/biomass ratio on gasification products was identified. A distribution kernel model is shown to resolve local particle over-loading problem.